Organisation of production of sterilisation equipment at a small machine-building enterprise - Sushko, Volodymyr; Desyk, Mykola; Gubenia, Oleksii (My University, 2024)
The article considers the peculiarities of organisation of work of small and medium-sized enterprises engaged in production of equipment for the pharmaceutical industry and medicine.

Розглянуті особливості організації роботи підприємств малої та середньої потужності із виробництва обладнання для фармацевтичної галузі та медицини.
Keywords: small and medium-sized enterprises; equipment; pharmaceutical industry; steam steriliser; підприємства малої та середньої потужності; обладнання; фармацевтична галузь; стерилізатор паровий; кафедра машин і апаратів харчових та фармацевтичних виробництв